To get the answer for this problem, first get all the x's on one side of the equation. You do that by subtracting 2x from each side. That gets you

-x+4 = 3 (because x-2x is -x)

Then you want to get all the numbers on the other side of the equation. To do that, subtract 4 from each side. That gets you

-x = -1 (because 3-4 is -1)

Now to make your x positive, multiply both sides by -1. That gets you

x = 1

And that's your answer.

x + 4 = 2x + 3

In order to solve this we need to isolate x

x + 4 = 2x + 3

x + 4 - 2x = 2x + 3 - 2x (subtract 2x from both sides)

-x + 4 = 3

-x + 4 - 4 = 3 - 4 (subtract 4 from both sides)

-x = -1

**x = 1 Answer.**

x +4=2x +3 In order to solve for x you are going to subtract both sides by 3.

x +4 -3=2x +3 -3 The 3 on the left side will cancel out.

x +1 = 2x Now you are going to add to subtract x on both sides.

x +1 -x = 2x -x The xx will be canceled out on the left side.

1 = x Here is the answer.

**x+4=2x+3**

Subtract **X** from both sides **4=x+3**

Subtract 3 from both sides to get X alone **x=1**

*Answer =* * X=1*

x + 4 = 2x + 3

First get the " x " on one side to, so subtract " x " on both sides

By subtracting, your equation should look like

**4 = x + 3 **now subtract 3 on both sides to get " x " alone

By subtracting, your equation should look like

**1 = x **which is your answer

x + 4 = 2x + 3

To solve this equation try to get all the " x " on one side. So, subtract x on both sides.

By subtracting, your should get

**4 = x + 3 **now subtract 3 on both sides to get " x " alone

By subtracting you should get

**1 = x ** which is your answer

x+4=2x+3

(combine the like terms)

(get the x alone in one side)

x+4=2x+3

(subtract x to the other side)

4=x+3

(subtract 3 to get the 3x alone)

1=x